PTU-111 A Prospective Study of Intravenous Paracetamol Prescribing and its use in Patients at Risk of Iatrogenic Paracetamol Induced Hepatotoxicity. (4th June 2013) - Evans, J A; Sampaziotis, F; Ismail, D; Baillie, S; McGrath, J
Abstract : Introduction: Intravenous (iv) paracetamol can cause severe hepatotoxicity and lead to death if inappropriately prescribed 1 . It is increasingly being used for post-operative pain and pyrexia 2 . There is a lack of awareness that paracetamol should be prescribed by weight when used in certain higher risk groups 1, 2 ; including those weighing less than 50kilos and in malnourished patients 3 . This study assessed iv paracetamol prescribing in patients at increased risk of hepatotoxicity. Methods: Drug charts and medical records from 5 wards (3 surgical and 2 medical including 1 gastroenterology ward) were assessed prospectively over 3 days. All patients prescribed paracetamol were identified; those receiving iv preparations were included. The age, sex and weight were recorded in conjunction with the dose, route and number of paracetamol doses received by each patient. Intravenous doses were identified by countersignatures on drug charts or where iv was the only route indicated. Medical records were reviewed for a history of alcohol excess, chronic liver disease, chronic kidney disease (CKD), eating disorders, and those taking CYP450 inducing medications. Results: 59 patients were receiving paracetamol via any route. The average age was 74.6 years old (range 32–86). 25 patients had received iv paracetamol with 12/25 (48%) receiving the drug only via the iv route. The mean number of consecutive doses was 4.44 (range 1–28). 3 patients had CKD, 3 patients were on the CYP450 inducer Rifampicin and 1 patient had an eating disorder and CKD. 2 patients receiving iv doses were under 50 kg, one of which had CKD. Of the 9 patients deemed to be at risk of iatrogenic paracetamol induced hepatotoxicity, 0% had paracetamol prescribed at the recommended reduced dose of 3g per day. Conclusion: This study demonstrates that intravenous paracetamol was not being prescribed appropriately. Intravenous paracetamol should be reduced in high risk groups to 3g per day (15mg/kg/24 hours). With 25–37% of all hospital inpatients being deemed at risk of malnourishment4 a large patient cohort is at risk of paracetamol induced liver injury. Assessment of nutritional status and improved awareness of higher risk patients is needed to avoid iatrogenic paracetamol induced hepatotoxicity through poor prescribing. Disclosure of Interest: None Declared References: Fatal Accident Inquiry into the death of Danielle Welsh. Available at: http://www.scotland-judiciary.org.uk/10/715/ [Accessed15 Nov 2012] Gray T, Hoffman R, Bateman D. Intravenous paracetamol – an international perspective of toxicity. Clinical Toxicology 2011; 49 : 150–152. British National Formulary. Sept 2012.64 : 264–265 BAPEN 2012 -http://www.bapen.org.uk/about-malnutrition/introduction-to malnutrition?showall = &start = 4, [Accessed 3rd Jan 2013].